Prediction of Positive Surgical Margins in Sinonasal Tract Squamous Cell Carcinoma - Yujiro Fukuda; Hidenori Suzuki; Nobuhiro Hanai; Hitoshi Hirakawa; Taijiro Ozawa; Eiichi Sasaki; Yasushi Yatabe; Hiroshi Yamashita; Yasuhisa Hasegawa (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Background: In patients with clinical T4 (cT4) squamous cell carcinoma (SCC) of sinonasal tract who received surgery, the relationship between positive surgical margins and positive clinical N stage as diagnosed by the presence of cervical lymph node metastasis has not been investigated so far. Therefore, we investigated the relationship between positive surgical margins and preoperative parameters in patients with cT4 SCC of the sinonasal tract following surgery.  Methods: Forty-one patients who underwent surgery for cT4 SCC of the sinonasal tract were investigated and survival rates were calculated using the Kaplan-Meier method. The relationship between surgical margins and preoperative parameters was analyzed.  Results: Both positive surgical margins and clinical N stage were significantly correlated with shorter survival rate by log-rank test.  Conclusion: Positive surgical margins can be predicted based on clinical N stage in patients with cT4 SCC of the sinonasal tract.